2004
DOI: 10.1016/j.humpath.2004.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Atypical goblet cell hyperplasia in congenital cystic adenomatoid malformation as a possible preneoplasia for pulmonary adenocarcinoma in childhood: a genetic analysis

Abstract: Congenital cystic adenomatoid malformation (CCAM) of the lung is a congenital lesion that is sometimes complicated by bronchioloalveolar adenocarcinoma (BAC). In some cases foci of atypical goblet cell hyperplasia (AGCH) can be found within the cysts. It has been proposed that CCAM and AGCH predispose to the development of BAC. The present study used comparative genomic hybridization (CGH) to screen 22 cases of CCAM (epithelium, surrounding normal lung tissue, and both preneoplastic and neoplastic lesions) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 13 publications
2
53
0
5
Order By: Relevance
“…[14][15][16][17] In the current study, we found 24 cases of adenocarcinoma displaying transition foci from the normal ciliated columnar cell to mucous columnar cell metaplasia, dysplasia, adenocarcinoma in situ, and finally invasive adenocarcinoma. Transition foci of normal ciliated columnar epithelium to mucous columnar cell were observed in bronchiole or honeycomb spaces.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[14][15][16][17] In the current study, we found 24 cases of adenocarcinoma displaying transition foci from the normal ciliated columnar cell to mucous columnar cell metaplasia, dysplasia, adenocarcinoma in situ, and finally invasive adenocarcinoma. Transition foci of normal ciliated columnar epithelium to mucous columnar cell were observed in bronchiole or honeycomb spaces.…”
Section: Discussionmentioning
confidence: 97%
“…[14][15][16][17] Mucous or goblet cell proliferation has been observed in or around congenital cystic adenomatoid malformation, and those mucous columnar cells have genetic abnormalities such as loss of heterozygosity at P16 INK4 or gain/loss of chromosomes, in contrast to relatively normal lungs. 15 On the basis of our recent experience of an adenocarcinoma that displayed an extensive transition from normal ciliated columnar cell to mucous columnar cells, indicative of a spectrum from dysplastic to malignant morphology, we were compelled to consider the possibility that mucous columnar cell metaplasia and dysplasia is another obvious pathway of pulmonary adenocarcinoma. Because mucous columnar cell metaplasia arises in the bronchus or bronchiole, it seems reasonable to think that adenocarcinoma arising through mucous columnar cell change belongs to the so-called central adenocarcinoma or non-terminal respiratory unit type adenocarcinoma, and not to the terminal respiratory unit type adenocarcinoma or peripheral adenocarcinoma.…”
mentioning
confidence: 99%
“…rhabdomyosarcoma in children [27][28][29][30] and mucinous BAC (mostly in adults) [31][32][33][34][35][36][37][38][39][40]. These associations have been significantly underappreciated and it is unlikely that they represent random associations or publication bias.…”
Section: From Cpam To Bac and Acmentioning
confidence: 99%
“…In 1998, Ota et al [17], having previously noted gastric mucins in mucinous BAC, studied 12 out of 26 cases of CPAM type 1 containing mucous cells and found mucins similar to those of the mucinous BACs. This association has been supported by the finding of similar genetic abnormalities (including gains in chromosomes 2 and 4) in both CPAM type 1 goblet cells and the cells of BAC [18]. Most recently, Ioachimescu and Mehta [14] described the 15-yr course of the development of a BAC (diagnosis at age 6 yrs, along with CPAM type 1), which subsequently developed into an invasive adenocarcinoma.…”
Section: Does Cpam Type 1 With Mucinous Foci Predispose To Bac?mentioning
confidence: 85%